A Review on Antidiabetic Medicinal Plants and Marketed Herbal Formulations - Malvi, Reetesh (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTDiabetes mellitus is a major problem of today?óÔé¼Ôäós world and leading cause of death. The number of people suffering from diabetes is increasing due to population growth, aging, urbanization, and increasing prevalence of obesity and physical inactivity. Indians are genetically more susceptible to diabetes, for which World Health Organization predicts the number of diabetic persons in India may rise up to 74 million by 2025. The increasing worldwide incidence of diabetes mellitus in adults constitutes a global public health burden. It is predicted that by 2030, India, China and the United States will have largest number of people with diabetes. So the need arises to cure this disease with potent drug causing fewer side effects. The plant based medicinal system is very useful since a long time for treatment of diabetes. It is necessary to emphasize plant based study because allopathic system has more side effects; however they are potent antidiabetic agents. Many of the herbs are available having antidiabetic activity and shows their action by different mechanism like stimulating or regenerating the effect on ?Ä?? cell or extra pancreatic effect for hypoglycemic activity. The 60% of the patient uses traditional system of medicine in India for treatment of diabetes. This article presents a review on some reported antidiabetic medicinal plants (with their botanical name, common name, constituent and mechanism of action for antidiabetic action) and plant based marketed herbal formulations.Key words: Diabetes, Antidiabetic herbs, Medicinal plants, Hypoglycemic medicinal plants.